Ojk And Dps Supervision From Sharia Economic Law Perspective - Hidayat, Taufik; Majdidin, Rijah Muhammad; Nur, Efa Rodiah (ASAS, 2023)
The OJK supervision system for Sharia banking can be implemented in three ways, namely providing permits, integrating all provisions, and integrating one-stop licensing. In the context of Islamic law, the OJK supervision system in Sharia banking consists of two aspects, namely providing rules and regulations related to banking management and licensing through OJK regulations, as well as direct and indirect supervision in collaboration between the OJK and the National Sharia Council (DSN) to form a Board. Sharia Supervisor (DPS) who will supervise banking compliance with the Sharia principles used.In supervising Sharia banking, OJK acts as the Al-Hisbah Institution, which is a supervisory institution that oversees market operations. The DPS formed by OJK and DSN acts as Muhtasib, which is assigned to carry out direct supervision of each Sharia bank. However, OJK only gives authority to DPS to control and assess the implementation of Sharia concepts in the Sharia banking sector and does not have the authority to provide provisions, policies, or penalties in supervising the implementation of activities in Sharia banks.To support the development of the Sharia economy in Indonesia, DPS, which acts as Muhtasib in supervising Sharia banking, needs to be given special authority apart from controlling and assessing, namely also providing policies and provisions related to licensing before and during activities in the sharia banking sector.Keywords: Sharia Economic Law, OJK, DPS, and Sharia Banking